Nutritional enhancement of whole grain bario rice by phytic acid degradation during germination - Lee, Huei Hong (2015)
Whole grain rice is suggested to be a better solution against the polished form with more vitamins, minerals and fiber than its processed equivalent. Abundance of phytic acid in whole grain rice demotes the nutritional values of whole grain rice in general, although its beneficial properties were also reported. Various strategies had been conducted to counteract the nutritional limitations in whole grain rice, including germination. These led to the main objective of this study, to determine the nutritional quality in whole grain rice of Bario rice cultivars and later improve the targeted nutritional quality through the germination process. Thirty rice cultivars named as “Adan” or “Bario” were assessed for nutrient bioaccessibility and antioxidant properties. The studies showed an acceptable level of in vitro digestibility in starch (193.77 ± 93.09 mg maltose released/g) and protein (69.01 ± 8.06%), but were poor in antioxidant properties and bioaccessibility of minerals (Phy/Fe 125.37 ± 38.95, Phy/Zn 201.97 ± 80.54 and Phy/Ca 11.58 ± 3.35). Most of the lowland Bario rice with medium grains had relatively better nutrient bioaccessibility while pigmented rice had high amounts of phenolic compounds (0.64 ± 0.21 mg GAE/g) and antioxidant properties. The drawback in the whole grains were related to relatively low mineral content (24.30 ± 0.46 g Fe/100g, 1.30 ± 0.35 g Zn/100g, 13.30 ± 2.79 g Ca/100g ) and high phytic acid content (24.29 ± 4.07 g/kg) in general, and also low phenolic content in non-pigmented rice (0.10 ± 0.04 mg GAE/g). The relationship between intrinsic phytic acid content, nutrient bioaccessibility and antioxidant properties was studied. Results suggested that intrinsic phytic acid could be an important chelating antioxidant (51.92 ± 8.35%, r = 0.32) in non-pigmented rice which also reduced mineral bioaccessibility in the whole grains. Phytic acid content significantly influenced mineral bioaccessibility (r =0.40 [Phy/Fe], r =0.27 [Phy/Zn], r = 0.60 [Phy/Ca]) especially iron and calcium. In vitro digestibility of starch and protein were not affected by intrinsic phytic acid content. The contribution of phytic acid to the antioxidant properties of whole grain rice was low, but phytic acid remains as an important antioxidant in non-pigmented rice. These imply that the antinutrient effects from phytic acid were stronger and significantly contributed to the low mineral bioaccessibility in the collection. Phytate degradation based on changes in phytic acid content, phytase activity and phytate globoids were investigated under various germination treatments in selected rice cultivars. This study showed that germination treatments facilitated the hydrolysis of phytate complexes in whole grain rice significantly, reducing phytic acid content (0.73 - 99.99% loss), accelerating phytase activity (0.38 – 270 U/kg increment) and releasing minerals from phytate globoids. However, the phytate degradation differed with rice cultivars under the same germination conditions. Germination is a suitable treatment for phytate degradation in Bario rice cultivars with the right germination conditions. The study was continued with optimization of germination conditions by response surface methodology in the cultivar Tuan. Phytic acid content was significantly reduced (1.24 – 99.99% loss) with facilitation of phytase activity (27.43 – 165.3 U/kg increment) during germination and led to increments in mineral bioaccessibility (8.03 – 239.56% Ca, 25.38% Fe, 1.18 – 45.01% Zn). Soaking for 12 hours under acidic condition (pH 2) was the most suitable for improvement of calcium and zinc bioaccessibility at room temperature (25°C). However, longer germination duration (50 hours) was required for higher iron bioaccessibility. Optimized germination conditions of pH 2.7, at 25°C and 12 hours germination successfully reduced phytic acid content and phytic acid to minerals mole ratio, and led to an increase in mineral bioaccessibility in calcium, iron and zinc. In conclusion, the whole grain rice of Bario rice cultivars had the advantages in in vitro digestibility of starch and protein but with limited mineral bioaccessibility and antioxidant properties. The limitations in mineral bioaccessibility were due to the abundance of phytic acid content in the whole grain rice. Phytate degradation in whole grain rice was cultivar and condition dependent. Optimized germination condition could promote phytate degradation and result in improved mineral bioaccessibility in selected whole grain Bario rice. Germinated whole grain rice with better mineral bioaccessibility can be a good substitution of whole grain rice as part of healthy diets.